Analyzing Collaborative Governance Dynamics in Kendalbulur Village Development, Tulungagung Regency - Hanif Muzaqi, Ajie; Junari; Ayu Rahmawati, Dyah (JPSI (Journal of Public Sector Innovations), 2023)
The collaborative governance framework today can be used to solve the complexity of the government's problems. One of the problems that can be addressed by implementing collaboration is the development of more prosperous and independent villages. This study aims to analyze collaborative governance practices in village development in relation to village fund budget management. This research was conducted in Kendalbulur Village, Tulungagung Regency, with a qualitative deductive approach, so the primary data was obtained through in-depth interviews and observations. The result of this study is that the implementation of collaborative Governance in Kendalbulur Village faces various dynamics, one of which starts from the content of the village fund policy itself. The interpretation of the village development policy still results in a double argument about whether the village fund policy is to develop more partial rural areas or build more empowerment-oriented villages. This interpretation will later impact the collaboration process between networks of actors in Kendalbulur village so that the established pattern of collaboration will be more complex. The results of collaborative-based village development must consider the starting conditions and dynamics that occur to make institutional design a determinant in the development of Kendalbulur Village.